Introduction and Contributions of the Communal Integration Business Model to Meet the Demand for Organic Rice: Case Study of Organic Rice in Banyumas - Saputro, Wahyu Adhi; Dewati, Rosita (AgriDev, 2025)
Lifestyle and health issues are important indicators in consuming food, especially organic rice. It is no wonder that the demand for organic rice has increased alongside the development of the era. The organic polemic is also one of the things that consumers consider in buying rice. This also happens in the Banyumas community, which has a group of farmers who cultivate organic rice. This research aims to see how significant the contribution of organic rice produced by farmers in Banyumas is and to provide recommendations in the form of introducing a business model for a communal integration system between organic rice farmers. The method used for analysis in this research is the descriptive statistics and contribution analysis. This research was conducted in Kalisube Village and Dawuhan Village in Banyumas District. The data used is on land area, rice production, and conversion to organic rice production. Using contribution analysis helps  to determine the significance of the assumed demand for organic rice in the long term when all people consume organic rice. Based on the research results, it was found that the contribution of organic rice in Dawuhan Village was greater than in Kalisube Village. The research results also state that when 15 percent of Banyumas people consume organic rice, there will be a shortage in meeting the demand for organic rice. Communal system business model is a step in solving the problem with shortage. The combination of cooperation and interaction between organic rice farmers in Banyumas Regency is essential to meet the demand for organic rice in the community.